Echocardiographic Manifestation of Esophagitis Mimicking a Posterior Mediastinal Mass. Issue 8 (January 2014) - Swarup, Supreeya; Kantamneni, Sowmya; Kabir, Sarah; Zeltser, Roman; Makaryus, Amgad N.
Incidental extracardiac findings (ECFs) are commonly noted on cardiac imaging. The majority of the ECFs are noticed on computed tomography (CT), cardiac magnetic resonance scanning, and myocardial perfusion imaging. Although transthoracic echocardiography (TTE) is a widely used cardiac modality, there is scarcity of data describing ECF on TTE. ECFs have the potential to alter patient management. We present a rare case of a cystic mass seen in the posterior mediastinum on TTE, which led to further evaluation and diagnosis of esophagitis with ulceration.